Claudin-7 expression in human epithelial ovarian cancer. Issue 6 (1st October 2008) - Tassi, R. A.; Bignotti, E.; Falchetti, M.; Ravanini, M.; Calza, S.; Ravaggi, A.; Bandiera, E.; Facchetti, F.; Pecorelli, S.; Santin, A. D.
Abstract : Claudin-7 (CLDN-7) is a tight junction protein recently found highly differentially expressed in ovarian carcinoma. To evaluate its potential as a novel biomarker, in this study, we quantified and compared claudin-7 expression at messenger RNA and protein level in 110 patients harboring various histologic types of epithelial ovarian carcinomas (EOC). CLDN-7 transcript was found significantly overexpressed in both primary and metastatic EOCs compared to normal human ovarian surface epithelium cell lines (fold change = 111.4, P < 0.001) by reverse transcription–polymerase chain reaction. At the protein level, CLDN-7 expression was found significantly higher in tumors of primary and metastatic origin when compared to normal ovaries ( P < 0.001), regardless of the histologic type, the grade of differentiation, and the pathologic stage of the disease ( P = 0.12). Moreover, a strong immunoreactivity for CLDN-7 was detected in EOC cells present in ascites fluids, whereas ascites-derived inflammatory cells, histiocytes, and reactive mesothelial cells were negative. Finally, immunohistochemical expression of CLDN-7 was observed in several human normal epithelial control tissues analyzed. CLDN-7 is significantly overexpressed in all main histologic types of EOC and in single neoplastic cells disseminated in peritoneal cavity and pleural effusions, suggesting its potential role as novel diagnostic marker in ovarian cancer. Despite widespread expression of CLDN-7 in several human normal tissues, the high density of CLDN-7 molecules, their membranous localization on EOC cells, and their lack of expression on the celomic epithelium in the peritoneal cavity suggest that this target could be potentially suitable for antibody-mediated localized therapies of ovarian adenocarcinoma.